2008
DOI: 10.1128/cvi.00200-08
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Glucan, Chitin, and Saccharomyces cerevisiae Mannan as New Biomarkers of Candida albicans Infection That Complement Tests Based on C. albicans Mannan

Abstract: Antibodies against Saccharomyces cerevisiae mannan (ASCA) and antibodies against synthetic disaccharide fragments of glucans (ALCA) and chitin (ACCA) are biomarkers of Crohn's disease (CD). We previously showed that Candida albicans infection generates ASCA. Here, we explored ALCA and ACCA as possible biomarkers of invasive C. albicans infection (ICI). ASCA, ALCA, ACCA, and Candida mannan antigen and antibody detection tests were performed on 69 sera obtained sequentially from 18 patients with ICIs proven by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 53 publications
1
44
0
2
Order By: Relevance
“…Whether this effect of Candida is also relevant for inflammatory bowel disease in humans is not clear. However, because Abs toward C. albicans were shown to be associated specifically with Crohn's disease, one may speculate that Candida plays a role in this disease (37). It is attractive to hypothesize that this has to do with the priming effect described in this article.…”
Section: Discussionmentioning
confidence: 83%
“…Whether this effect of Candida is also relevant for inflammatory bowel disease in humans is not clear. However, because Abs toward C. albicans were shown to be associated specifically with Crohn's disease, one may speculate that Candida plays a role in this disease (37). It is attractive to hypothesize that this has to do with the priming effect described in this article.…”
Section: Discussionmentioning
confidence: 83%
“…[42][43][44][45][46][47][48][49][50][51][52][53][54][55] The number of IC cases per study varied from 7 to 105, with a median of 25. A control group was included in 11 of 14 studies, and most frequently consisted of patients with similar risk factors but without IC, and sometimes with other documented infections.…”
Section: Mannan Ag (Mn)/anti-mannan Ab (A-mn)mentioning
confidence: 99%
“…The β-(1,3)-glucans are well-known pro-inflammatory agents [13,14] and innate immune responses can be induced through binding to monocytes or macrophages via the receptor dectin-1 [15] or complement receptor 3 (CR3) [16]. Adaptive immune responses to β-glucan have received much less attention, but anti-β-(1,3)-glucan antibodies have previously been reported [17,18] and their measurement has been suggested useful for the diagnosis of candidiasis [19]. Recently Chiani et al [20] reported high anti-β-glucan IgG levels in human sera, in a study on the use of β-glucans in vaccines.…”
Section: Introductionmentioning
confidence: 99%